ANALISIS KETERKAITAN KECERDASAN EMOSIONAL TERHADAP AKHLAK MAHMUDAH SISWA KELAS IV SDN LENTENG AGUNG 01 - Karima, Litakuna; Lathifah Nasywa Nabilah (STKIP Subang, 2026)
This research is motivated by a phenomenon occurring in elementary schools, where elementary school students still experience difficulties in managing their emotions, are easily provoked, tease their peers, and are unable to develop empathy. This indicates the need for attention to children's intelligence development. This study aims to analyze the relationship between emotional intelligence and the morals of Mahmudah, a fourth-grade student at SDN Lenteng Agung 01.This study used a qualitative approach with descriptive methods. Data collection techniques were conducted through interviews, participant observation, and documentation with Islamic Religious Education teachers and fourth-grade students at SDN Lenteng Agung 01. The collected data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing.The research results show that emotional intelligence plays a significant role in the development of students' morality. Students who are able to recognize and control their emotions tend to demonstrate patience, respect for their peers, and demonstrate social awareness. Supporting factors in the development of emotional intelligence include the role of Islamic Religious Education (PAI) teachers, parental support, and a positive classroom environment. Obstacles faced include differences in student character, lack of emotional control, and teachers' limited time for individual guidance. Therefore, strengthening emotional intelligence needs to be an integral part of moral education in elementary schools.